A case–control study of respiratory medication and co‐occurring gastrointestinal prescription burden among persons with Ehlers–Danlos syndromes. Issue 4 (12th November 2021) - Bascom, Rebecca; Dhingra, Radha; Francomano, Clair A.; Schubart, Jane R.
Abstract: We previously reported increased pain and gastrointestinal (GI) medication prescription claims among persons with Ehlers–Danlos syndromes (EDS) and peripubertal increase in opioid and anti‐emetic claims among women with EDS. Herein, we hypothesized a higher proportion of respiratory and co‐occurring respiratory and GI medication prescription claims among persons with EDS compared to their matched controls with increases among peripubertal women with EDS. We compared the proportions of respiratory and co‐occurring respiratory and GI medication prescription claims among persons with EDS (aged 5–62) against their age‐, sex‐, state of residence‐, and earliest claim date‐matched controls using 10 years of private prescription claims data. Prescription claims among persons with EDS versus matched controls were increased for eight medication classes ( p < .0001): intranasal/inhaled corticosteroids (ICS) (30.8% vs. 19.0%), oral steroids (30.0% vs. 16.5%), H1‐antihistamines (26.2% vs. 12.2%), short‐acting beta agonists (22.7% vs. 11.6%), decongestants (21.6% vs. 15.9%), leukotriene modifiers (8.9% vs. 3.6%), ICS/long‐acting beta agonists (5.7% vs. 2.9%), muscarinic antagonists (2.5% vs. 0.9%), and co‐occurring prescriptions (29% vs. 10%). Our results suggest a critical time window for peripubertal intervention and research and a need to focus on the pathogenesis and clinical evaluation of EDS‐specific respiratory and aerodigestive disorders.